Synthesis of C1-Substituted Oxabenzonorbornadienes - Haner, Jamie; Jack, Kelsey; Menard, Michelle L.; Howell, Jennifer; Nagireddy, Jaipal; Raheem, Mohammed Abdul; Tam, William (Synthesis, 2012)
Oxabenzonorbornadienes are valuable synthetic intermediates because they can serve as a general template with which to create highly substituted ring systems. However, to date, only very few C1-substituted oxabenzonorbornadienes have been reported. In this study, the synthesis of some C1-substituted oxabenzonorbornadienes was achieved by the Diels–Alder reaction between 2-substituted furans and benzyne. Moderate to good yields (16–80%) of the Diels–Alder reactions were observed. These C1-substituted oxabenzonorbornadienes will find applications as valuable synthetic intermediates and should be useful in studies of transition-metal-catalyzed reactions.
Keywords: cycloaddition; Diels–Alder reaction; benzyne; furan; alkenes